(untitled) (Ocean and Coastal Research, 2024)
Dimensions of particulate matter found in the water column of marine and freshwater environments (thepelagic realm) range from nanometers to tens of meters. Included in this enormous size range are miniaturebacteria, phytoplankton (photosynthetic microalgae), mixoplankton (mixotrophic microorganisms), micro- tometer sized drifting animals (zooplankton), plastic particles, detrital aggregates and fecal pellets, fish, whalesand many others. These particles and organisms are involved in many different processes and perform amultitude of services, such as in oceanic biogeochemistry (carbon fixation, oxygen production, carbon exportand others) or human nourishment (fisheries). Digital optical tools used in pelagic imaging approaches nowallow to bridge this enormous size span and to image micro- to meter-sized objects in situ or on discretesamples. Monitoring plankton, nekton, and particle dynamics at spatial and temporal scales that enableeffective management of marine and freshwater environments poses a collective challenge for society. Wehere argue that a global, distributed and operational network for pelagic imaging is needed and within reach,and we provide recommendations how it can be attained via the voluntary activities of the pelagic imagingcommunity and strategic support from funding agencies and other stakeholders.